STUDI KOMPARATIF PRESTASI BELAJAR BAHASA ARAB SISWA ANTARA LULUSAN MADRASAH DENGAN NON-MADRASAH DI KELAS VII MTs MA’HAD AL-ZAYTUN - Feny Intan Kurnia; Dewi Utami; Iis Humaeroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educational background has the potential to influence learning outcomes due to differences in previous academic experiences. The number of madrasah graduates in the seventh grade of MTs Ma'had Al-Zaytun in the 2023/2024 academic year is higher than that of non-madrasah graduates. In theory, students with a madrasah educational background have an advantage in learning Arabic. However, there appears to be a lack of enthusiasm among students in attending classes, which has an impact on learning outcomes. This study aims to analyze the differences in Arabic learning achievements between madrasah and non-madrasah graduates and to identify the factors that influence them. The research uses a mixed methods approach with an explanatory sequential pattern. The quantitative stage is carried out first and reinforced through qualitative analysis. The comparative quantitative approach uses probability sampling with a proportionate stratified random sampling type. The sample consisted of 80 students (53 madrasah graduates and 27 non-madrasah graduates). Data collection techniques included observation, tests, and interviews. Data analysis was performed using the T-test. A qualitative approach was conducted through interviews with teachers. The results of the study showed a significance value (Sig. 2-tailed) of 0.703. Thus, the null hypothesis (H0) was accepted, and the alternative hypothesis (Hₐ) was rejected. It can be concluded that there is no significant difference in Arabic learning achievement between madrasah and non-madrasah graduates in grade VII MTs Ma'had Al-Zaytun. Qualitative analysis results reveal factors that influence learning achievement, namely students' initial abilities, learning methods, learning motivation, and academic readiness.